Home Literacy of Dual-Language Learners in Kindergarten From Low-SES Backgrounds. (April 2018) - Wood, Carla; Fitton, Lisa; Rodriguez, Estrella
This study aimed to describe home literacy (HL) activities of Spanish-/English-speaking children of low–socioeconomic status backgrounds and examine the relationship between HL and performance on standardized assessments. Parents of 65 dual-language learners (DLLs) in kindergarten completed an HL questionnaire. Parents reported an average of 17 books at home and engaged in active HL activities for 24 minutes a day on average. The relations between HL activities and performance were evaluated using correlations and regression. Analyses revealed a significant relation between HL and children's language abilities, as measured by a bilingual measure of morphosyntax and semantics. Children's reported interest in reading was also positively associated with their phonological awareness skills. HL was significantly related to child interest in reading and language performance. These findings suggest that home literacy plays a role in the language and literacy development of DLLs.